A nação e seus outros: uma leitura subalterna de Os Sertões de Euclides da Cunha - Pimentel, Talita Cristina (2010)
The present work presents a subordinate reading of Os Sertões of Euclides da Cunha also informed for sources of the Brazilian social thought and the incursion in the historical archives on the episode of Canudos. This at the beginning crystallized a true moral panic of the Republic. Euclides of the Wedge told the revolt of Canudos as a shock between races where the miscegenation gained a fincado historical clipping in the binary division of the Brazilian society in caboclos x mulatos (or interior x the coast). One underlines the panic that account of the Brazilian society with regard to the racial mixture between whites and blacks took and the fear moral of that the life in the cities would be a degenerative threat for our nationality. From this division racial of the society established for Euclides - and endorsed for intellectuals, politicians and artists in the consolidation of the Republic - the hinterland and its people if consecrate as the place and the citizens of a genuine nationality. This allowed, also, that the others were established, the undesirable one in the formation of the Brazilian nationality.